Comparative detectability of follicles and corpus luteum through rectal-palpation and ultrasonography in buffaloes during different stages of estrous cycle - HONPARKHE, M; GANDOTRA, V K; NANDA, A S (The Indian Journal of Animal Sciences, 2014)
The ovaries of 18 normal cycling buffaloes were scanned ultrasonographically during different stages of estrous cycle to study the size of follicle and corpus luteum CCL) and to fmd the comparative detectability of the same by rectal palpation and ultrasonography. The buffaloes were divided in to 3 groups (each containing 6 animals) depending upon the parity, viz. nulliparous (group 1), primiparous (group 2) and pluriparous (group 3). Rectal palpation and ultrasonography were performed in all the buffaloes at estrus (day 0), met-estrus (day 2), mid diestrus (day 9) and late diestrus (day 16). The follicles were detected in 60.5, 22.0 and 24.5% of the buffaloes during estrus, mid diestrus and late diestrus respectively, by palpation per rectum as compared to those in 100, 55.0 and 77.0% of the buffaloes on corresponding stages by ultrasonography. The CL were detected by rectal palpation in 33.0, 88.0 and33.0% of the buffaloes on days 2, 9 and 16, respectively, as compared to those in 88.0 and 33.0% of the buffaloes by ultrasonography on corresponding days. Mid cyclic CL was better detected by both the techniques; however, ultrasound could better detect the CL on days 2 and 16 of the cycle than by rectal palpation. Irrespective of the parity ofthe animals, ultrasonographic mean size (n= 18) of the follicle at estrus and the CL at mid diestrus were 1.06+-0.20 cmand 1.14+-0.21 cm respectively. The foUiqie and CL less than 0.90 cm of size was not detected most of the times by palpation per rectum.